Microparticle optical trapping of silica gel by Au-NP Q-switched fiber laser pulses - Mahmud, N.N.H.E.N.; Awang, N.A.; Zulkefli, N.U.H.H.; Hanafiah, F.N.M. (Elsevier, 2023)
This study demonstrates a method for microparticle optical trapping of silica gel using a stable Q-switched fiber laser (QFL) pulse. Gold nanoparticle (Au-NP) were fabricated as saturable absorbers on a side-polished optical fiber (SPF) to achieve stable QFL pulses of frequencies 25.81 kHz. Silica gel microparticles with a radius of 300–400 μm produced a dissimilar attractive trapping force based on the viscous drag exerted on the light field of the QFL. Shifts were observed at wavelengths of 1533.8–1541.0 nm and frequencies of 25.81–28.87 kHz. The validity of the numerical model is proven and the proposed model can be applied to examine the behavior of surface plasmon polaritons (SPP) modes in microparticle optical trapping. These findings confirm that the proposed system facilitates absorption microparticle trapping at the 1540 nm wavelength region.